Chemically reacting mixing in coaxial miscible liquid jets under variable viscosities and reaction rates. (15th March 2023) - Zhang, Bo; Usta, Mustafa; Khan, Irfan; Ranjan, Devesh; Aidun, Cyrus K.
Highlights: Multiscalar mixing in a chemically reactive miscible two-fluids system. A parametric study by varying the viscosity and reaction rate constant ratios. Inverse correlation between undesirable product and the desirable product. Reaction fronts for different reaction rate constant and viscosity ratios. Optimum reaction route with higher conversion efficiency of the desirable product. Abstract: We study the mixing and reactions between two fluids with disparate viscosities in a co-axial flow at high Schmidt number, through numerical simulations. The chemical reactions chosen in this work are competitive-consecutive in nature. Numerical implementation of the reactions proceeds as given by Li and Toor (1986), in a Large-Eddy Simulation (LES) framework. The aim of the present study is to investigate the effect of reaction rate constant ratio on the product and byproduct formations under distinct viscosity ratios between the annular and central jets. Flow features promoting mixing and reactions such as turbulence, engulfment, jet instability, waves and break-up are described. The effect of viscosity difference between the jet and co-flow on the mixing and reactions are also delineated. It is found that selectivities of the undesirable product decrease with reducing viscosity ratio as well as increasing reaction rate constant ratio.